Localized B-0 shimming based on Na-23 MRI at 7 T - Gast, Lena; Henning, Anke; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2019)
Purpose To validate the feasibility of localized B-0 shimming based on B-0 maps acquired with sodium (Na-23) MRI. Methods A localized B-0 shimming routine based on a constrained regularized algorithm in combination with Na-23 MRI data acquired with a 3D density-adapted radial readout scheme was implemented on a 7T MR system. Measurements were performed using a dual-tuned Na-23/H-1 head coil. The quality of B-0 maps reconstructed from Na-23 images and the resulting shim values was examined depending on the acquisition duration between 10 minutes and 15 seconds to examine clinical applicability. The B-0 shimming based on Na-23 B-0 maps was performed both for phantom and human head of 6 healthy volunteers, and the resulting B-0 homogeneity was compared with the vendor-provided H-1 MRI-based gradient-echo brain shimming routine. Results The proposed Na-23 MRI-based shimming routine showed a reduction in B-0 variation comparable to the vendor-provided shim both in phantom and in vivo measurements. Within the examined multicompartment phantom, the B-0 variations could be reduced by up to 77% using the Na-23 MRI-based shim. In human head, B-0 variations were reduced by approximately 50% using an acquisition time of 15 seconds for the Na-23 B-0 maps and only 1 iteration of B-0 shimming. Conclusion The Na-23 MRI-based localized B-0 shimming is possible at 7 T within clinically acceptable acquisition durations (< 1 minute). It was shown that using the proposed Na-23 MRI-based shimming approach, the Na-23 image quality at ultrahigh field strength can be strongly improved.
CRIS-Team WoS Importer:2019-10-22